Effects and Perceptions of Game-Based Formative Assessment on Vocabulary Acquisition in EFL Primary Classrooms in the UAE - ALABEDI, FARAH (2023)
In foreign language classes, vocabulary acquisition plays a crucial role in improving learners' language skills as it directly impacts their ability to communicate effectively in the target language. However, many EFL students face challenges in acquiring vocabulary which has created a recurring issue in language learning. This mixed methods study investigated the effects of GBFA (Quizlet) on EFL students’ vocabulary acquisition. It also aimed at investigating students’ perceptions about the use of GBFA (Quizlet) for vocabulary learning and explored EFL teachers’ perceptions about using GBFA (Quizlet) in teaching the new vocabulary words among EFL primary age students in a private school in Abu Dhabi/United Arab Emirates. The quantitative data was gathered through employing pre- and post- tests as well as a questionnaire. While the qualitative data was obtained by conducting semi-structured interviews with 6 EFL primary teachers. Constructivist learning theory, input-process-outcome game-based learning model, computer assisted language learning (CALL), mobile assisted language learning (MALL), and technology acceptance model (TAM) were used as theoretical frameworks to understand the impact of GBFA, specifically Quizlet, on students’ vocabulary learning to get a holistic picture of students’ as well as teacher’s perceptions of the implementation of Quizlet for vocabulary learning. The findings revealed that there was a significant effect of employing Quizlet on students' vocabulary acquisition. The questionnaire responses indicated that the majority of students had positive perceptions of Quizlet, considering it user-friendly, easy to navigate, and beneficial for enhancing their vocabulary learning. Students also expressed a strong intention to continue using Quizlet for vocabulary learning. Furthermore, the interviews conducted with EFL teachers confirmed a consensus among them regarding the positive effect of Quizlet on vocabulary learning. Limitations and recommendations were addressed based on the main results of this research.